Efeito da marinação enzimática e ultrassom na qualidade de peito de frango amadeirado ‘wooden breast’ - Lima, Juliana Lopes de (2021)
Wooden breast (WB) is a myopathy seen in fast-growing birds, the visual appearance, functionality and texture of the chest muscle, making it more rigid. The objectives of this research were to evaluate the effect of the combined use of the enzyme papain and ultrasound on marinating under texture and physical quality, chemical and technological analysis of WB chicken breast. To assess the effects of the enzyme concentration papain (0.1; 0.2; 0.3%) and the time in the ultrasound (10; 20; 30 min) in marinating, the complete 2² factorial design was used with 3 repetitions at the central point and the dependent variable was the shear force (SF). The marinated breast with ideal texture condition (MWB), PWB chicken breasts without ultrasound, WB and Normal were evaluated for physical-chemical quality and technological properties. The SF of the WB meat close to that of the Normal breast was obtained when using 0.2% papain and 20 min of ultrasound. The use of the enzyme papain in marinating WB meat has significantly reduced (p <0.05), by up to 48% (MWB) its hardness, with no effect of the use of ultrasound or of the enzyme: ultrasound interaction being observed within the studied range. Marinating reduced the chewiness of cooked WB meat; however, the isolated use of papain gave the meat greater adhesiveness, and a pasty consistency on the surface. The marinated samples (MWB and PWB) were associated with a higher moisture content, collagen and solubility of myofibrillar proteins. From a technological point of view, marinating reduced weight loss when cooking WB meat, making it similar (p <0.05) to normal meat. The measures of lipid oxidation showed low values of TBARS in the treatments marinated after cooking and in the quantification of carbonyl compounds. Overall, WB chicken meat marinated with papain (with / without ultrasound) presented texture and technological properties similar to those of Normal meat, with reduction in protein and lipid oxidation parameters. However, the use of papain without application ultrasound proved to be a more efficient alternative to improve the texture of WB chicken breasts.